2022
DOI: 10.21203/rs.3.rs-1856600/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exclusive breastfeeding intention and associated factors in pregnant women: findings from a population-based study

Abstract: Background The benefits of breastfeeding especially exclusive breastfeeding have been well recognized. Aim To investigate the prevalence and influencing factors of exclusive breastfeeding intentions for the first six months among pregnant women. Methods A self-designed questionnaire was adopted to collect information on maternal intention on exclusive breastfeeding and other related social characteristics. The primary outcome was intention of mother on exclusively breastfeeding which derived by a response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Breastfeeding is important for promoting the growth and development of infants and young children and improving the health of mothers and infants [1] .The breastfeeding rate of 6 months in China is 29%, far lower than the world average (41%) [2] . China's maternal willingness to breastfeed is high, but the breastfeeding rate will decrease with the prolongation of breastfeeding duration [3] , and eventually mothers will give up breastfeeding early for social and psychological reasons. Research has shown that [4,5] breastfeeding motivation is an important factor in maternal initiation of breastfeeding, and according to the self-determination theory, it is believed that breastfeeding motivation is in uenced by the mother's self-determination.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is important for promoting the growth and development of infants and young children and improving the health of mothers and infants [1] .The breastfeeding rate of 6 months in China is 29%, far lower than the world average (41%) [2] . China's maternal willingness to breastfeed is high, but the breastfeeding rate will decrease with the prolongation of breastfeeding duration [3] , and eventually mothers will give up breastfeeding early for social and psychological reasons. Research has shown that [4,5] breastfeeding motivation is an important factor in maternal initiation of breastfeeding, and according to the self-determination theory, it is believed that breastfeeding motivation is in uenced by the mother's self-determination.…”
Section: Introductionmentioning
confidence: 99%